PIMS 인증결함의 보완조치 우선순위에 관한 연구 - 강다연(Da-Yeon Kang); 전진환(Jin-Hwan Jeon); 황종호(Jong-Ho Hwang) (한국콘텐츠학회 논문지, 18(4), 2018)
Most of the privacy officers of organizations are hard to think of the corrective action about deficiencies of the PIMS(Personal Information Management Systems) certification. Because, it is difficult to define the priority of the complementary measures due to the unique characteristics and procedures of personal information protection for each organization. The purpose of this study is to evaluate the priority of the complementary measures using the Analytic Hierarchy Process(AHP). According to the results, it is important to comply with the legal requirements in the first tier. The second tier, PIMS experts answered that dedicated organization, password management, and agreement of the subject are important. Above all, agreement of the subject was found the highest priority for complementary measures about PIMS's deficiencies. 대다수의 국내 기업 개인정보보호 담당자는 방송통신위원회가 인정하는 개인정보보호 관리체계(PIMS) 인증 취득에 난이도가 존재한다고 판단한다. 이는 사업자마다 개인정보취급에 대한 고유한 특성과 업무절차가 반영되어 정형화된 업무를 규정하기 힘들고, 인증취득을 위해 거치는 여러 과정에서 인증컨설턴트, 인증심사원의 경험에 상당부분 의존할 수밖에 없기 때문이다. 결과적으로 인증취득 실무경험이 부족한 담당자는 PIMS 인증 초기에 무엇을 우선적으로 이행하고 준비해야 하는지에 많은 난관에 부딪히게 된다. 본 연구에서는 계층적 의사결정 기법(AHP)을 통해 인증취득 실무담당자의 PIMS 인증결함의 보완조치 우선순위를 살펴봄으로서 향후 PIMS 인증취득을 원하는 기업이나 인증결함에 따른 보완조치 시 담당자가 우선적으로 선행할 부분을 검토하고자 한다.